Elastisitas Permintaan Tenaga Kerja dan Kekakuan Upah Riil Sektoral di Sulawesi Selatan - nFN Mahyuddin; Majdah M. Zain (Jurnal Agro Ekonomi, 2010)
EnglishThis study aimed to measure the elasticity of labor demand and the level of real wage rigidity as well as studying the dynamic behavior of real wages in South Sulawesi. The elasticity of labor demand were analyzed using an OLS method, the level of wage rigidity was analyzed using an error correction model (ECM), and dynamic behavior of real wages was analyzed using an impulse response function (IRF). The results showed that the elasticity of labor demand was inelastic to the real wages in all sectors. The elasticity of labor demand of the changes in a variety of sources of economic growth was also inelastic in all sectors. The employment opportunities in agricultural and industrial sectors were more responding to the increasing exports and investment, while other sectors more responding to the increased private consumption. Labor productivity and imports significantly reduced employment opportunities in all sectors. The industrial sector had a more real wages rigidity compared to the real wages in agricultural sector and other. Real wages rigidity of industrial sector took about 4.6 years to reach equilibrium conditions, while the agricultural sector only took about 1.5 years and other sectors needed about 2.2 years. The increased competitiveness of various exported commodities and the creation of a conducive-investment climate were a strategic step to expand employment opportunities. In addition, the policy such as setting the regional minimum wage (UMR) more suitable to market wages was also considered as a strategy to reduce wage rigidity in South Sulawesi.IndonesianStudi ini bertujuan untuk mengukur elastisitas permintaan tenaga kerja dan tingkat kekakuan upah riil serta mempelajari perilaku dinamis upah riil sektoral di Sulawesi Selatan. Elastisitas permintaan tenaga kerja dianalisis dengan metode OLS, tingkat kekakuan upah menggunakan Error Correction Model (ECM) dan perilaku dinamis upah riil menggunakan metode Impuls Respon Function (IRF). Hasil menunjukkan bahwa elastisitas permintaan tenaga kerja terhadap upah riil adalah inelastis di semua sektor. Elastisitas permintaan tenaga kerja atas perubahan berbagai sumber-sumber pertumbuhan ekonomi juga inelastis di semua sektor. Kesempatan kerja sektor pertanian dan industri lebih merespon peningkatan ekspor dan investasi sedangkan sektor lainnya lebih merespon peningkatan konsumsi masyarakat. Produktivitas tenaga kerja dan impor signifikan mereduksi kesempatan kerja di semua sektor. Lebih lanjut, sektor industri memiliki upah riil yang lebih kaku di bandingkan upah riil sektor pertanian dan sektor lainnya. Upah riil sektor industri membutuhkan waktu sekitar 4,6 tahun untuk mencapai kondisi keseimbangannya sedangkan sektor pertanian hanya memerlukan waktu sekitar 1,5 tahun dan sektor lainnya sekitar 2.2 tahun. Peningkatan daya saing komoditi ekspor dan penciptaan iklim investasi yang kondusif merupakan langkah strategis untuk perluasan kesempatan kerja. Selain itu, kebijakan seperti penetapan UMR yang lebih sesuai dengan upah pasar juga dipandang strategis untuk mengurangi kekakuan upah di Sulawesi Selatan.